Ultrasound effect in the removal of intraradicular posts cemented with different materials - Berbert, Fabio Luiz Camargo Vilella [UNESP]; Espir, Camila Galletti [UNESP]; Crisci, Fernando Simões; Andrade, Marcelo Ferrarezzi de [UNESP]; Chávez-Andrade, Gisselle Moraima [UNESP]; Leonardo, Renato de Toledo [UNESP]; Saad, José Roberto Cury [UNESP]; Segalla, José Claudio Martins [UNESP]; Vaz, Luiz Geraldo [UNESP]; Basso, Keren Cristina Fagundes Jordão [UNESP]; Dantas, Andrea Abi Rached [UNESP] (Jaypee Brothers Medical Publishing, 2015)
This study evaluated the effect of ultrasonic vibration on the tensile strength required to remove intraradicular post cemented with different materials. Bovine teeth were selected, and 7 mm of the cervical root canals were prepared to size 5 Largo drill, the posts were cemented with zinc phosphate, Enforce (resin) or Rely X (glass ionomer). The specimens were divided into six groups (n = 10), according to the following procedures: GI-cementation with zinc phosphate associated with traction force; GII-cementation with zinc phosphate associated with ultrasonic activation and traction force; G111-cementation with Enforce associated with traction force; GIV-cementation with Enforce associated with ultrasonic activation and traction force; GV-cementation with Rely X associated with traction force; and GVI-cementation with Rely X associated with ultrasonic activation and traction force. The tensile test was conducted using the electromechanical testing machine, the force was determined by a specialized computer program and ultrasonic activation using the Jet Sonic Four Plus (Gnatus) device in 10P. Concerning to average ranking, GI showed statistically significant difference in comparison with GII and GVI (p < 0.05); there was no statistical difference in GIII and GIV when compared to other groups (p > 0.05). The ultrasound favored the intraradicular post traction regardless of the employed cement in greater or lesser extent. The post removal is a routine practice in the dental office, therefore, new solutions and better alternatives are need to the practitioner. We did not find in the literature many articles referring to this practice. Thus, the results from this study are relevant in the case planning and to promote more treatment options.
Keywords: Dental cements; Tensile strength; Ultrasonics